Efficient synthesis of antifungal pyrimidines via palladium catalyzed Suzuki/Sonogashira cross-coupling reaction from Biginelli 3,4-dihydropyrimidin-2(1H)-ones - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Deshpande, Mukund V.; Srinivasan, Kumar V. (Tetrahedron, 2008)
An efficient regioselective approach to the synthesis of tetrasubstituted pyrimidines was developed by sequential functionalization of easily available Biginelli 3,4-dihydropyrimidine-2(1H)-ones via dehydrogenation, chlorination followed by palladium catalyzed C-C Suzuki/Sonogashira coupling reaction. All the synthesized compounds were evaluated in vitro for their antifungal activities against Candida albicans, Cryptococcus neoformans, Benjaminiella poitrasii, Yarrowia lipolytica, and Fusarium oxysporum, and antibacterial activities against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activities; Biginelli compounds; chlorination; Oxidation; Pyrimidines; Suzuki coupling